Studies on the mineral nutrition of the rice plant: XXI. Effects of mineral deficiencies and excesses on the activity of leaf nitrate reductase and grain protein (preliminary note) - Malavolta, E.; Parada, A.; Martins, G.; Gonçalves, J.C.; Centurion, J.F.; Vasconcellos, L.A.B.C.; Almeida, M.; Marchetti, M.E.; Pereira, O.A.; Buzetti, P.; Cabral, C.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
Rice plants, varieties IAC-164 and IAC-165 weree grown in number 2 Hoagland's solution, full strength, and with excess of Al and Cl. Nitrate reductase (RNO3) activity was assayed in the leaves one month before harvesting. When the grains were already dry, plants were harvested, the mineral contents of the organs was determined, and crude protein in the grains was also determined (semi micro Kjeldahl). Statistical analyses of the data thus obtained showed that enzymatic activity decreased when the plants were deficient in N, P, and K, as well as when the plants were deficient in N, P, and K, as well as when they had excess Al and Cl. Sulfur deficiency depressed RNO3 activity in variety IAC-164 only. Lack of Mg had the same effect in variety IAC-165. Crude protein in the grains decreased due to lack of N, P, Cu, and S, and to excess both of Al and Cl. In both varieties, however, the deficiencies of K and Mg had apparently the opposite effect. By putting together data from all treatments (except -K and -Mg) a positive correlation between leaf RNO3 activity and grain protein was found to exist.